(untitled) (INTERNATIONAL CONFERENCE ON MODERN DEVELOPMENT OF PEDAGOGY AND LINGUISTICS, 2025)
This paper investigates how artificial intelligence (AI) integrated into interactive learning platforms enhances English pronunciation among non-native speakers. Drawing upon pedagogical principles from the MA TESOL framework, the study identifies AI tools’ capabilities in offering personalized, immediate feedback and learner-driven pronunciation training. It presents qualitative and empirical evidence that AI tools improve both segmental and suprasegmental features of speech. The paper also discusses limitations, ethical concerns, and practical implications for TESOL practitioners seeking to incorporate AI into blended learning environments.